Determination of Characteristics Properties of Some Sunflower Seed in Erzurum and Iğdır Irrigated Conditions - SEFAOĞLU, Fırat (Alinteri Zirai Bilimler Dergisi, 2020)
This research was carried out between the years of 2015-2016 in order to determine the seed properties of some sunflower genotypes in Erzurum and Iğdır irrigated conditions. In this study seven type of (Coral, P4Ll62, Pactol, Lg5580, Tarsan, 08Tr003, Cadix) sunflower cultivars were used and grain length, width, thickness, dehulled seed (internal rate of grain) and shell ratio of the samples were examined. In this study significant were found the other features except seed width and thickness where some sunflower of grown in different location. In the designed location in Erzurum; grain length, width, thickness, dehulled seed were determined as 11.8–13.4 mm (Coral: P4Ll62), 5.8-6.2 mm (Coral: Lg5580 and Tarsan), 3.5-4.4 mm (Coral and Pactol: Cadix), 16.3-21.3 mm (Cadix: P4Ll62 and Tarsan 1018) and 56.3-76.3 mm (Tarsan and Cadix : P4Ll62). In the designated location in Iğdır, these values ranged between 11.5-14.2 mm (Coral: P4Ll62), 5.5-6.5 mm (Pactol: Tarsan 1018 and Cadix), 3.6-4.1 mm (Coral and Pactol: Cadix), 16.7-26.7mm (P4Ll62 and Pactol: Cadix) and 66.7-81.7 mm (Pactol: Cadix) respectively. According to these results, the designated location for this research in Iğdır come in to prominence in terms of the investigated properties.